A Christian ethics of blame: or, God says, "vengeance is mine" - Hartman, Robert J. (Religious studies, 2025)
There is an ethics of blaming the person who deserves blame. The Christian scriptures imply the following no-vengeance condition: a person should not vengefully overtly blame a wrongdoer even if she gives the wrongdoer the exact negative treatment that he deserves. I explicate and defend this novel condition and argue that it demands a revolution in our blaming practices. First, I explain the no-vengeance condition. Second, I argue that the no-vengeance condition is often violated. The most common species of blame involves anger; anger conceptually includes a desire for vengeance; and there are many pleasures in payback. Third, I clarify that it is possible to blame non-vengefully in anger and highlight three good uses for anger in non-vengeful blame. Fourth, I offer two reasons that justify the divine command prohibiting vengeance, and I note that the Christian God is merely sufficient to make non-vengeance morally obligatory. Fifth, I defend the no-vengeance condition against four biblical objections.